2022
DOI: 10.1002/arch.21949
|View full text |Cite
|
Sign up to set email alerts
|

PGE2 mediation of egg development in Western flower thrip, Frankliniella occidentalis

Abstract: Eicosanoids mediate various insect physiological processes, including reproduction. Especially, the eicosanoid prostaglandin E 2 (PGE 2 ) is known to mediate oocyte development in some insects. The explosive reproductive potential of the Western flower thrips, Frankliniella occidentalis, damages various agricultural crops. However, little is known about the underlying physiological processes of egg development in this pest. This study found that treatment with aspirin (ASP) (a specific cyclooxygenase (COX) inh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 33 publications
0
4
0
Order By: Relevance
“…occidentalis oogenesis. A recent study showed that prostaglandin mediates oocyte devilment in early and late stages in addition to the endocrine signals [ 35 ]. This suggests the oogenesis of F .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…occidentalis oogenesis. A recent study showed that prostaglandin mediates oocyte devilment in early and late stages in addition to the endocrine signals [ 35 ]. This suggests the oogenesis of F .…”
Section: Discussionmentioning
confidence: 99%
“…JH acid methyltransferase (JHAMT), JH esterase/ JH epoxide hydrolase, and Met involved in JH synthesis, JH degradation, and the JH receptor, DEGs between transcripts at 0 h and 36 h after adult emergence and 60 h AAE represents DEGs between transcripts at 0 h and 60 h after adult emergence. KEGG categories include alanine, aspartate and glutamate metabolism (1), amino sugar and nucleotide sugar metabolism (2), apoptosis (3), arachidonic acid metabolism (4), ascorbate and aldarate metabolism (5), autophagy (6), biosynthesis of amino acids (7), biosynthesis of cofactors (8), biosynthesis of nucleotide sugars (9), biosynthesis of unsaturated fatty acids (10), carbon metabolism (11), citrate cycle (12), cysteine and methionine metabolism (13), cytochrome P450 ( 14), ECM-receptor interaction (15), endocytosis (16), fatty acid biosynthesis (17), fatty acid elongation (18), fatty acid metabolism (19),folate biosynthesis (20), foxO signaling pathway (21), fructose and mannose metabolism (22), glutathione metabolism (23), glycerolipid metabolism (24), glycerophospholipid metabolism (25), glycine, serine and threonine metabolism (26), glycolysis/gluconeogenesis (27), inositol phosphate metabolism (28), longevity regulating pathway (29), lysine degradation (30), lysosome (31), MAPK signaling pathway (32), metabolic pathways (33), mitophagy (34), glycan biosynthesis (35), nicotinate and nicotinamide metabolism (36), nucleotide metabolism (37), oxidative phosphorylation (38), pentose and glucoronate interconversions (39), pentose phosphate pathway (40), phagosome (41), protein export (42), protein processing in endoplasmic reticulum (43), purine metabolism (44), pyruvate metabolism (45), starch and sucrose metabolism (46), steroid biosynthesis (47), thiamine metabolism (48), Toll and Imd signaling pathway (49), various types of N-glycan biosynthesis (50), vitamin B6 metabolism (51), and Wnt signaling pathway (52).…”
Section: Expression Profiles Of Genes Associated With Endocrine Signa...mentioning
confidence: 99%
See 1 more Smart Citation
“…Different reproductive modes along with a short lifecycle allow the thrips population to rapidly increase during early and late seasons, in which female progeny develop from fertilized eggs while males develop from unfertilized eggs [11,12]. The nutrient-based oogenesis of F. occidentalis is well-programmed in females by gonadotropic hormones including juvenile hormone, ecdysone, and prostaglandin [13,14]. To suppress thrips outbreaks, more than 20 kinds of chemical insecticides including organophosphate, carbamate, pyrethroids, neonicotinoids, avermectin, and spinosad are registered and applied to different agricultural crops [15].…”
Section: Introductionmentioning
confidence: 99%